Island size disrtibution under different substrate temperatures and film mass thickness - Gladkikh, N.T.; Dukarov, S.V.; Gabusu, P.A. (STC “Institute for Single Crystals”, 1994)
The technique of studying island size distribution versus different factors in films condensed via liquid phase has been developed. Distribution changes during growth of an island gallium film on amorphous carbon substrate have been examined. Temperature effects on microparticle size distribution in proximity of the maximum supercooling of tin condensates on carbon substrate have been investigated.
Keywords: Thin films; size distribution